‘If you can’t beat them, be them’ : A critical analysis of local streaming platform and Netflix alternative Streamz - Raats, Tim; Evens, Tom (MedieKultur: Journal of media and communication research, 2021)
Faced with heavy competition of global subscription-video-on-demand (SVOD) streaming services, along with increased pressure on fi nancing and distribution of domestic content, legacy media players are increasingly exploring the potential of local SVOD services as domestic alternatives to global platforms such as Netflix and Disney+, often in collaboration with other European broadcasters and/or distributors. This article presents an in-depth case study of Streamz, a domestic SVOD alternative launched in Belgium in September 2020. Building on scholarly work on media disruption and platform power, the case study examines the political and market context that shaped the existence of the platform, and critically analyses the strategies pursued by legacy media players in attempting to develop and emulate key competitive advantages of global SVOD players. The article demonstrates how a persistent policy push to collaborate in a small market resulted in an unusual joint venture and, at the same time, how diff erent market factors, most of them characteristic for small media markets, pose signifi cant challenges for domestic players to develop a profi table platform in Europe, let alone be able to stand a chance in a highly competitive streaming market.